Microbial Community Diversity and Structure within Organic and Conventional Farming Systems in Central Highlands of Kenya - Karanja, Edward (University of Embu, 2020)
Microbial diversity and function in agro-ecosystems is influenced by various aspects linked to soil and agronomic practices for example, tillage, irrigation, crop rotation and application of organic and inorganic inputs. Farming systems practices may affect the dynamic interactions existing between soil, plant and microorganisms in different agricultural biomes. Due to limitations associated with conventional microbial cultivation strategies, only a fractional number of cultivable species has been extensively studied. This study explored the effects of conventional versus organic farming systems on microbial communities. Soil samples were collected from an ongoing long-term farming system comparison trials established in 2007 at Chuka and Thika in Kenya. Illumina sequencing technology and analysis of 16S rDNA, 16S rRNA cDNA amplicons, fungal ITS and mRNA transcripts were used to determine the diversity, structure and function of bacteria, archaea and fungal communities within conventional and organic farming systems. Grouping of sequences into operational taxonomic units at 97% similarity was done using QIIME2 pipeline and taxonomy assigned via BLASTn against SILVA 128 and UNITE ITS database, and a curated database extracted from GreenGenes, RDPII and NCBI. Transcriptomes were analysed using Parkinson lab pipeline (https://github.com/ParkinsonLab/Metatranscriptome-Workshop). Statistical analysis was done using R programming language version 3.1.5 and Vegan Community Ecology Package version 2.5.2. R. The total number of OTUs obtained per dataset included 4,916 OTUs (16S rDNA), 530 OTUs (16S rRNA cDNA) and 1,128 OTUs (fungal ITS) at 97% genetic distance datasets, respectively. The most notable bacterial phyla within farming systems were Proteobacteria, Actinobacteria, Firmicutes Acidobacteria, Bacteroidetes, Chloroflexi, Cyanobacteria, Deinococcus-Thermus, Fusobacteria, Gemmatimonadetes, Planctomycetes and Verrucomicrobia. Farming systems in both sites were dominated by unassigned fungal phyla. The known fungal phyla revealed included Ascomycota, Basidiomycota, Chytridiomycota, Glomeromycota, Calcarisporiellomycota, Kickxellomycota and Mortierellomycota. Ascomycota was most abundant in organic farming systems while Chytridiomycota was dominant in conventional farming systems in both sites. Conventional farming systems had a higher species richness and diversity when compared with organic farming systems. Factors such as pH, C, N, Zn, Fe, Al, B and micro-aggregates were found to be the major drivers of microbial diversity within farming systems in both sites. Major metabolic pathways within the farming systems in both sites comprised of carbohydrates and energy metabolism, biodegradation and metabolism of xenobiotics and secondary metabolites biosynthesis. This shows that microbes in the farming systems utilize diverse carbon sources for survival, as revealed by metabolic processes and genes responsible for specific pathways. These findings indicate integration of organic and inorganic inputs, not only affect the soil chemistry but also the microbial population dynamics and their functional roles.
Thesis